Pterostilbene activates the GRP78–elF2α–ATF3 cascade of ER stress and subsequently induces apoptosis in human colon cancer cells. (October 2016) - Kim, Kui-Jin; Chei, Sungwoo; Choi, Seo-Yun; Lee, Ok-Hwan; Lee, Boo-Yong
Highlights: Ptero may act as natural anti-cancer material in human colon cancer. Ptero indicated by decreased the cell viability of HCT116, SW480, and LoVo cells. Altered S phase regulation by Ptero stimulates to undergo TCF4- and Cyclin D1- mediated apoptosis in HCT116 and SW480 cells. Evidence a mechanism by which Ptero increases GRP78–lF2α–ATF3 cascade of ER stress in human colon cancer cells. Abstract: Pterostilbene (Ptero), a major active compound of blue berries, is a natural antioxidant phytochemical which has a strong potential for cancer prevention and intervention. However, it has not been shown the detailed anti-cancer mechanism of action for Ptero which has not fully elucidated. In present study, we report that Ptero treatment in human colon cancer cells inhibits the cell cycle via the suppression of Cyclin D1 expression. This inhibition of Cyclin D1 was associated with changes in the TCF4 expression and activation of PARP cleavage. The induction of apoptotic cells by Ptero was observed by Hoechst staining. We also observed that Ptero promotes to delay S phase into G2/M phase cell cycle transition in colon cancer cells. Analysis of the gene expression profiles by western blotting revealed that Ptero increased the expression of GRP78 protein related to the unfolded protein response. This induction was associated with the activation of the eIF2α–ATF3 cascade of endoplasmic reticulum (ER) stress. Moreover, our result showed that p38MAPK is essential factor for Ptero-induced ATF3 expression. The current study shows that Ptero stimulates GPR78–eIF2α–ATF3 cascade and subsequently induces apoptosis. Our results therefore provide new insights into the molecular mechanisms of Ptero-induced cell death in human colon cancer cells and suggest Ptero might be a potential chemotherapeutic agent which is able to intervene and prevent the human colon cancer.